Understanding the role of water in the lyotropic liquid crystalline mesophase of high-performance flexible supercapacitor electrolytes using a rheological approach - Özkaynak, Mert Umut; Kocaaga, Banu; Dönmez, Koray Bahadır; Dağlar, Selin; Türker, Yurdanur; Karatepe, Nilgün; Güner, F. Seniha; Dag, Ömer (Elsevier BV, 2024)
The effect of water on the structure, properties, and flexibility of lyotropic liquid crystalline (LLC) C12E23-LiCl-H2O gel electrolytes was explored. Structural techniques, such as X-ray Diffraction (XRD), Polarized Optical Microscopy (POM), and five dynamic measurements, were employed to examine the rheological properties of the LLC mesophase across various water contents. These analyses provided quantitative insights into the influence of water content and LiCl concentration on gel strength, gelation point, and structural recovery. The three-dimensional network of the gel encapsulates Li+ and Cl− ions within hydrophilic domains, showing significant performance in supercapacitor applications. The observed increase in storage modules with decreasing water content is attributed to variations in the quantity and average size of junction points owing to system entanglement. These research findings highlight that excess water molecules, which break down micellar connections, are responsible for the weakening of the gel. Conversely, at low water concentrations, the micellar domains entangle, displaying viscoelastic behavior akin to that of a transitory polymer network.